Mekanisme Passive Cooling Box untuk Optimalisasi Baterai Konversi Sepeda Motor BBM Menjadi Sepeda Motor Listrik - Ian Hardianto Siahaan; Danny Purnama; Ninuk Jonoadji (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2024)
An important component of an electric motorcycle is the battery, which plays a role in storing energy through the principles of electrochemistry. Lead-acid and lithium-ion batteries are the two most common types of batteries found in electric vehicles. Electric motorcycle batteries typically range from 32 to 72 volts, depending on engine requirements, and have a storage capacity of 20 to 50 Ah. Batteries generally have internal resistance that causes temperature increases, which means that working at high temperatures will significantly decrease their life. Increased temperatures can also create heat leaks inside the battery, which can lead to major safety issues such as fires and explosions, as well as a loss of battery capacity. The working temperature should not be kept above 50 °C, whereas on lithium-ion batteries, it ranges between -30 °C and 40 °C. The aim of this research is to develop, manufacture, and test battery boxes with passive cooling to keep the battery temperature at the intended ideal level. The method applied is to set up a control system that can function to prevent overheating the battery. Based on the tests carried out on the passive cooling system, this managed to maintain the temperature of the lithium-ion battery when used at an average speed of 40–60 km/h.